Perancangan Monitoring Prototype kWh-Meter Prabayar Berbasis Short Message Service (SMS) - Kiki Purnama; Tri Rahajoeningroem (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2018)
Abstract - At the moment, people who use electricity as their daily necessities still use the methods that have been in the past, namely by purchasing an electric voucher that has been available several digits of code entered into the prepaid kWh meter via the keypad. This method is considered to be less effective and less efficient in a period that has experienced a lot of progress, especially in the field of technology. Especially when the electric pulse has reached the minimum limit of the prepaid kWh meter, it only gives a warning to the sound of the buzzer alarm, it can only be heard by the customer if he is inside the house. so that the customer cannot find out if the customer is out of the house. Automatically the kWh meter customer is not prepared to deal with it if the user is not at home. So from that the research that will be made is a prototype prepaid kWh meter based on Short Message Service (SMS). In addition to being able to control the remaining electricity pulses remotely, this tool will also be able to charge electric pulses without having to enter the voucher code into the kWh meter directly but with this tool the customer can fill in by sending a short message or SMS set by the customer. The system contained in this Short Message Service (SMS) prepaid kWh meter prototype is controlled by 16 ATM AVR Microcontrollers. When the prepaid kWh meter value shows a value of 5 kWh, the system automatically provides information on the remaining kWh meter electricity through short message or SMS and marked with the buzzer sound and LED indicator. That will be made is considered to be more effective and flexible. From the results of the research data that have been collected, it can be seen that the performance of SMS-based prepaid kWh meters with the overall test results is successful and the percentage of success almost reaches 100%. Keyword:’ Prepaid kWh Meter, Short Message Service (SMS), Buzzer, Microcontroller ATMega16.’